Evaluation of heterogeneous processes in the polar lower stratosphere in WACCM3 - Tilmes, S.; Kinnison, D. E.; Müller, R.; Sassi, F.; Marsh, D. R.; Boville, B. A.; Garcia, R. R. (Journal of Geophysical Research, 2007)
Chemical ozone loss in the polar lower stratosphere is derived from an ensemble of three simulations from the Whole Atmosphere Community Climate Model (WACCM3) for the period 1960-2003, using the tracer-tracer correlation technique. We describe a detailed model evaluation of the polar region by applying diagnostics such as vortex temperature, sharpness of the vortex edge, and the potential of activated chlorine (PAC1). Meteorological and chemical information about the polar vortex, temperature, vortex size, and activation time, and level of equivalent effective stratospheric chlorine, are included in PAC1. Discrepancies of the relationship between chemical ozone loss and PAC1 between model and observations are discussed. Simulated PAC1 for Antarctica is in good agreement with observations, owing to slightly lower simulated temperatures and a larger vortex volume than observed. Observed chemical ozone loss of 140 +/- 30 DU in the Antarctic vortex core are reproduced by the WACCM3 simulations. However, WACCM3 with the horizontal resolution used here (4 x 5) is not able to simulate the observed sharp transport barrier at the polar vortex edge. Therefore the model does not produce an homogeneous cold polar vortex. Warmer temperatures in the outer region of the vortex result in less chemical ozone loss over the entire polar vortex than observed. For the Arctic, WACCM3 temperatures are biased high (by 2-3 degrees in the annual average) and the vortex volume and chlorine activation period is significantly smaller than observed. WACCM3 Arctic chemical ozone loss only reaches 20 DU for cold winters, where observations suggest approximate to 80-120 DU.